Education Level, Occupational Classification, and Perceptions of Differences for Blacks in the United States. Issue 2 (June 2017) - Burns, Stephanie T.; Garcia, Gayle
Abstract : A random sample of 1, 276 U.S. adults were surveyed about their perceptions of differences for Blacks in the United States based on discrimination, ability to learn, opportunities for education, and willpower. Those with little education and extensive education were more aware of discrimination for Blacks. Higher levels of education as well as professional and managerial work increased awareness that Blacks have the same ability to learn as Whites and that Blacks lack equitable opportunities for an education. Those with less education and those employed in technical and manual labor were the most likely to say Blacks lacked willpower.